Game-changing restraint of Ros-damaged phenylalanine, upon tumor metastasis article - Gueron, Geraldine (2018)
An abrupt increase in metastatic growth as a consequence of the removal of primary tumors suggests that the concomitant resistance (CR) phenomenon might occur in human cancer. CR occurs in murine tumors and ROS-damaged phenylalanine, meta-tyrosine (m-Tyr), was proposed as the serum anti-tumor factor primarily responsible for CR. Herein, we demonstrate for the first time that CR happens in different experimental human solid tumors (prostate, lung anaplastic, and nasopharyngeal carcinoma). Moreover, m-Tyr was detected in the serum of mice bearing prostate cancer (PCa) xenografts. Primary tumor growth was inhibited in animals injected with m-Tyr. Further, the CR phenomenon was reversed when secondary implants were injected into mice with phenylalanine (Phe), a protective amino acid highly present in primary tumors. PCa cells exposed to m-Tyr in vitro showed reduced cell viability, downregulated NFκB/STAT3/Notch axis, and induced autophagy; effects reversed by Phe. Strikingly, m-Tyr administration also impaired both, spontaneous metastasis derived from murine mammary carcinomas (4T1, C7HI, and LMM3) and PCa experimental metastases. Altogether, our findings propose m-Tyr delivery as a novel approach to boost the therapeutic efficacy of the current treatment for metastasis preventing the escape from tumor dormancy.